The Effect of Ease of Use, Usefulness, Trust, and Security on Decisions Using M-Banking Bank Syariah Indonesia - Hasyim, Fuad; Sari, Intan; Rahayu, Nanik (BanKu: Jurnal Perbankan dan Keuangan, 2023)
This study aims to analyze the effect of ease of use, usefulness, trust, and security to decision using m-banking Bank Syariah Indonesia. This study used a questionnaire to collect data and reach 100 respondents. The respondent is a customer who uses m-banking Bank Syariah Indonesia. Sample determination uses simple random sampling method, and the analysis method using multiple linear regression analysis. The results of this study are usefulness, trust, and security variables influence the decision to use m-banking Bank Syariah Indonesia. In contrast, the ease of use does not affect the decision to use m-banking Bank Syariah Indonesia. These findings indicate that the m-banking system needs to be upgraded to minimize cases of transaction errors, bugs and slow access.